Coral reef rehabilitation following Hurricane Irma using nano-engineered artificial reefs in Sint Maarten - Emily Higgins; Kyralai Duppel; Megan Connell; Guyon Brenna; Konstantin Sobolev (PeerJ)
Artificial reefs are being increasingly deployed as a coral reef restoration strategy. Additional reef habitats made from conventional substrates (e.g., metal, concrete, etc.) have had limited success in addressing conservation objectives on degraded coral reefs due to structure size and lack of standardized monitoring, and inability to enhance select ecological, and species variables. Technological advances and new restoration methods must be quickly tested and applied on a large scale to curb further deterioration of coral reefs. Here, we present the results of the first deployment of Oceanite artificial reefs (ARs). We compare the composition of the benthic community and associated fish assemblages on Oceanite ARs 14 months after deployment in a marine protected area (MPA) and two unprotected sites in Philipsburg, Sint Maarten. We also examined fish abundance and behaviour on the ARs. The initial results from this pilot study suggest that Oceanite mineral matrices can enhance local biodiversity, attract coral recruits, provide food and protection for large fish communities, and develop an early stage, healthy coral reef community in 14 months. We suggest that further research and testing of Oceanite capabilities will allow us to develop site-, species-, and function-specific nanotechnology-enabled substrates to optimize AR conservation goals. Oceanite mix designs can be tuned to precise parameters to promote reef restoration and stressor mitigation (e.g., pH, leachate emissions, surface texture, porosity, void structure, and hydrophobic, heat-absorbing, and disease-fighting properties). Using both bottom-up and top-down restoration processes, we suggest that deploying bio-enhancing habitats with targeted microclimate stressor treatments on the world’s critical reefs will allow to build global refuges resilient to climate change and provide much needed ecosystem services.